Mathematical Modelling of Portable Solar Water Distillation System - Sahoo, U.; Singh, S. K.; Kumar, R.; Kumar, P. (Journal of Technology Innovations in Renewable Energy, 2015)
Portable Solar Water Distillation (PSWD) system can provide drinking water and hot water simultaneously to households. It utilizes solar radiation to heat the water and produce fresh water out of the saline or brackish water & also produce hot water. The paper focuses mainly on field performance of a new design of PSWD for domestic applications in remote and hilly areas. Field Performance data of PSWD system has been recorded during summer and winter in northern region. It is observed that on Solar Global Radiation 2.3 kWh/ 0.25 m2, maximum output of distilled water generation of 1.2 liters/day per 0.25 m2 was achieved and average temperature of hot brackish water has reached 420C at ambient temperature of 230C within 8 hours. This system is the most efficient and cost effective. It can produce pure, clean fresh water along with hot brackish water from any water source.